Simulasi Dan Analisis Performansi Vehicular Ad Hoc Network (VANET) Menggunakan Protokol Routing Berbasis Topologi Di Kota Pekanbaru - Mutia Indah Lestari; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
VANET is a subset concept of Mobile Ad-Hoc Network (MANET) where the vehicle acts as a node on the network. The basic purpose of VANET is to support communication between vehicles so that it can be used as an intelligent traffic information traffic system. This communication can be done directly between vehicles (Vehicle to Vehicle) or with the infrastructure to communicate. High node mobility is a basic VANET characteristic that causes rapid changes in network topology. This necessarily requires the implementation of a routing protocol that matches its characteristics within the network. In this study to support the performance of VANET communication is used topology-based routing Ad hoc On-Demand Distance Vector (AODV). AODV is one of the reactive routing protocols in VANET. The AODV protocol will be simulated using Network Simulator-2 (NS-2) by multiplying the number of nodes scenario that runs on the real map. This scenario will be analyzed and reviewed from the parameters of Packet Delivery Ratio, End to End Delay and Routing Overhead. The simulation results obtained on each parameter are 99.20%; 0.0138 seconds; 19076 packet.Keywords: AODV, VANET, SUMO, NS-2, 802.11p